Copeptin associates with cause-specific mortality in patients with impaired renal function: results from the LURIC and the 4D study - Krane, Vera; Kleber, Marcus E.; März, Winfried; Delgado Gonzales de Kleber, Graciela (Clinical chemistry, 2017)
Background: In chronic kidney disease (CKD) arginine vasopressin (AVP) cannot efficiently act via renal V2-receptors. AVP is upregulated leading to augmented activation of V1a- and V1b-receptors, which might contribute to the increase in cardiovascular and infectious complications in CKD. Here, we evaluate copeptin, a surrogate of AVP, and its association with cause specific mortality among patients within the whole spectrum of renal function. Methods: Copeptin was measured in baseline samples from the LURIC (n = 3131 patients with coronary angiograms) and the 4D-Study (n = 1241 type 2 diabetic hemodialysis patients). Patients were stratified into 4 groups: estimated glomerular filtration rate (eGFR) ≥90 mL/min/1.73 m2, 60-89 mL/min/1.73 m2, <60 mL/min/1.73 m2, and hemodialysis. The association of copeptin with mortality was assessed by Cox proportional hazards regression during 9.9 years of median follow-up in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study and 4 years of median follow-up in the German Diabetes Dialysis Study (4D-Study). Results: Median copeptin increased with decreasing eGFR: 5.6 [interquartile range (IQR), 3.1-8.1] pmol/L (eGFR ≥90 mL/min/1.73 m2), 6.7 (2.9-10.5) pmol/L (eGFR 60-89 mL/min/1.73 m2), 15.3 (6.7-23.9) pmol/L (eGFR <60 mL/min/1.73 m2), and 80.8 (51.2-122) pmol/L (hemodialysis), respectively. Per SD increase in copeptin, the risk of coronary, infectious, and all-cause mortality increased by 25, 30, and 15% [hazard ratios (HR), 1.25; 95% CI, 1.13-1.39; HR, 1.30; 95% CI, 0.98-1.71; and HR, 1.15; 95% CI, 1.05-1.25], respectively, in patients with eGFR 60-89 mL/min/1.73 m2. Except for coronary death, results were similar among patients with more advanced renal disease. No significant association was found in patients with normal renal function. Conclusions: Copeptin concentrations were independently associated with coronary, infectious, and all-cause mortality in patients with renal impairment. In patients with normal renal function no significant association was found.